Optimal Population and Capital over Time: The Maximin Perspective - Calvo, Guillermo A. (Review of Economic Studies, 1979)
Journal Article Optimal Population and Capital over Time: The Maximin Perspective Get access Guillermo A. Calvo Guillermo A. Calvo Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 1, January 1979, Pages 59–71, https://doi.org/10.2307/2297172 Published: 01 January 1979 Article history Received: 01 January 1977 Accepted: 01 May 1978 Published: 01 January 1979